Recognition of One-, Two-, and Three-Pair Dichotic Digits under Free and Directed Recall - Strouse, Anne; Wilson, Richard H. (Journal of the American Academy of Audiology, 1999)
A one-, two-, and three-pair dichotic digit test was administered to 180 subjects (20-79 years) with varying degrees of hearing sensitivity. The test was carried out under free- and directed-recall response conditions. The results indicated that recognition performance decreased as a function of increasing age. Statistical analysis using analysis of covariance indicated that differences in performance between age groups were not owing to differences in hearing sensitivity. Thus, with the effects of hearing sensitivity removed, age alone accounted for a significant portion of the variability in the data among age groups. Normative data for the free-recall condition are reported for the two lists of randomly interleaved one-, two-, and three-pair digits included on the Tonal and Speech Materials for Auditory Perceptual Assessment, Disc 2.0 (1998) compact disc. A comparison of performance in free- and directed-recall conditions indicated three patterns of results. First, 58 percent of the subjects had normal recognition performance for one-, two-, and three-pair digits under both recall conditions. Second, 39 percent of the subjects had a deficit in the free-recall condition, with normal performance in the directed-recall condition, which was interpreted as representing primarily a cognitive problem. Third, the remaining 3 percent of the subjects showed a deficit in both free- and directed-recall conditions, which was attributed primarily to an auditory problem.Abbreviations: ANCOVA = analysis of covariance, ANOVA = analysis of variance, CD = compact disc, rau = rationalized arcsine unit
Keywords: Aging; auditory perception; compact disc; dichotic listening tests; speech perception; uncertainty